ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMP PADA PELAJARAN IPA SAAT PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Much. Solikhin; An Nuril Maulida Fauziah (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study aims to analyze the critical thinking skills of junior high school students when learning online. This research is a descriptive study with a quantitative approach. The research subjects were 20 students of class IX-C SMP Negeri 62 Surabaya. The research data collection technique used ten multiple choice questions. The sampling technique in this study was purposive sampling technique. The data analysis technique used in this research isprocessing descriptive statistical. The results showed that critical thinking skills in interpretation skills had a percentage of 53.00% in the medium category, analysis skills had a percentage of 61.67% in the high category, inference skills had a percentage of 30.00% with a low category, explanation skills had a percentage of 20.00. % in the very low category. The ability to think critically of class IX-C SMP Negeri 62 Surabaya during online learning as a whole has a percentage of 45.7%, including in the medium category.